Genetic Algorithm IQA Data - Michael Anastasios Mardikes (21762611) (2025)
This data is relevant to the pre-print: Michael A Mardikes, John T Evans, Nathan C Sprague, et al. Foreground and Background Image Quality Optimization for Improved Sim2Real Transfer in Synthetic Vision Systems. TechRxiv. May 23, 2025. DOI: 10.36227/techrxiv.174802987.74303969/v1